Characterization of phosphorus availability in response to radial oxygen losses in the rhizosphere of Vallisneria spiralis. (October 2018) - Han, Chao; Ren, Jinghua; Wang, Zhaode; Yang, Shika; Ke, Fan; Xu, Di; Xie, Xianchuan
Abstract: The viewpoint that radial oxygen loss (ROL) of submerged macrophytes induces changes in redox conditions and the associated phosphorus (P) availability has been indirectly confirmed at larger spatial scales using conventional, destructive techniques. However, critical information about microniches has largely been overlooked due to the lack of satisfactory in situ mapping technologies. In this study, we deployed a recently developed hybrid sensor in the rhizosphere of Vallisneria spiralis ( V. spiralis ) during two vegetation periods to provide 2-D imaging of the spatiotemporal co-distribution of oxygen (O2 ) and P from a fixed observation point. Overall, the images of O2 and P showed a high degree of spatiotemporal heterogeneity throughout the rhizosphere at the sub-mm scale. A clear decrease in the P mobilization corresponded well to the steep O2 enhancement within a 2-mm- thick zone around younger V. spiralis root, indicating a significant coupling relationship between ROL and P availability. Surprisingly, despite significant diurnal shifts in ROL along the older V. spiralis roots, P availability did not fluctuate in a substantial part of the rhizosphere throughout the day; however, ROL increased the P immobilization significantly by changing the redox gradients at the outer rhizosphere. This study clearly demonstrates how continuous ROL of V. spiralis can play a major role in regulating P availability within the rhizosphere. The premise behind this statement is the discovery of how this continuous ROL can lead to the formation of three distinctive redox landscapes in the rooting sediment (oxic, suboxic, or anaerobic layers). Graphical abstract: Image 1 Highlights: DO concentration and P flux in V. spiralis rhizosphere were imaged simultaneously. Observed heterogeneous co-distribution of O2 and P availability, mediated by roots. Diurnal rhythms of O2 and P availability around V. spiralis roots were documented. Direct evidence showed unequivocal P immobilization affected by radial oxygen loss.